Novel genetically-modified chimpanzee adenovirus and MVA-vectored respiratory syncytial virus vaccine safely boosts humoral and cellular immunity in healthy older adults. Issue 5 (May 2019) - Green, Christopher A.; Sande, Charles J.; Scarselli, Elisa; Capone, Stefania; Vitelli, Alessandra; Nicosia, Alfredo; Silva-Reyes, Laura; Thompson, Amber J.; de Lara, Catherine M.; Taylor, Kathryn S.; Haworth, Kathryn; Hutchings, Claire L.; et al.
Highlights: There is no licensed vaccine to prevent severe disease caused by respiratory syncytial virus (RSV) infection. RSV is a major cause of hospitalisation and death in the elderly. The novel viral-vectored vaccines PanAd3-RSV and MVA-RSV appeared safe and boosted both humoral and cellular RSV-specific immune responses in healthy older adults. The magnitude of immune responses to vaccination appeared similar to what was observed in younger adults. Abstract: Objectives: Respiratory syncytial virus (RSV) causes respiratory infection across the world, with infants and the elderly at particular risk of developing severe disease and death. The replication-defective chimpanzee adenovirus (PanAd3-RSV) and modified vaccinia virus Ankara (MVA-RSV) vaccines were shown to be safe and immunogenic in young healthy adults. Here we report an extension to this first-in-man vaccine trial to include healthy older adults aged 60–75 years. Methods: We evaluated the safety and immunogenicity of a single dose of MVA-RSV given by intra-muscular (IM) injection ( n = 6), two doses of IM PanAd3-RSV given 4-weeks apart ( n = 6), IM PanAd3-RSV prime and IM MVA-RSV boost 8-weeks later ( n = 6), intra-nasal (IN) spray of PanAd3-RSV prime and IM MVA-RSV boost 8-weeks later ( n = 6), or no vaccine ( n = 6). Safety measures included all adverse events within one week of vaccination and blood monitoring. Immunogenicity measures included serum antibody responses (RSV- and PanAd3-neutralising antibody titres measured by plaque-reduction neutralisation and SEAP assays, respectively), peripheral B-cell immune responses (frequencies of F-specific IgG and IgA antibody secreting cells and memory B-cells by ex vivo and cultured dual-colour ELISpot assays respectively), and peripheral RSV-specific T-cell immune responses (frequencies of IFNγ-producing T-cells by ex vivo ELISpot and CD4+/CD8+/Tfh-like cell frequencies by ICS/FACS assay). Results: The vaccines were safe and well tolerated. Compared with each individual baseline immunity the mean fold-changes in serum RSV-neutralising antibody, appearance and magnitude of F-specific IgG and IgA ASCs and expansion of CD4+/CD8+ IFNγ-producing T-cells in peripheral circulation were comparable to the results seen from younger healthy adults who received the same vaccine combination and dose. There were little/no IgA memory B-cell responses in younger and older adults. Expansion of IFNγ-producing T-cells was most marked in older adults following IM prime, with balanced CD4+ and CD8+ T cell responses. The RSV-specific immune responses to vaccination did not appear to be attenuated in the presence of PanAd3 (vector) neutralising antibody. Conclusions: PanAd3-RSV and MVA-RSV was safe and immunogenic in older adults and the parallel induction of RSV-specific humoral and cellular immunity merits further assessment in providing protection from severe disease.